2016
DOI: 10.3847/0004-6256/152/6/211
|View full text |Cite
|
Sign up to set email alerts
|

Are There Moonlets Near the Uranian Α and Β Rings?

Abstract: The Voyager 2 Radio Science Subsystem occultations of the Uranian α and β rings exhibit quasiperiodic optical depth variations with radial wavelengths that vary with longitude. These patterns may be wakes from small moonlets orbiting exterior to these rings. Based on the observed structures in the rings, we estimate that the moonlets would need to be located ∼ 100 km exterior to the rings' semimajor axes (106 +22 −12 km for α and 77 +8 −4 km for β) and be 2 − 7 km in radius. Such moonlets could help keep the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…At λ = 0.2µm, the great distances D of Uranus (19.2 AU) and Neptune (30 AU) from Earth prevent ground-based or Earth-orbit-based stellar occultations from obtaining better resolution than about 750 m and 950 m, respectively. Given that wave-like variations in the dense rings have sub-kilometer wavelengths (Chancia & Hedman 2016;Horn et al 1988), we expect resolutions of order 200 m is needed to see any planetgenerated waves. This resolution threshold, combined with the number of cuts required to uniquely determine the number of arms, which is of order the relevant m (about 20 for the waves of interest here), implies that the detection of planetary normal modes via wave identification will have to await an orbiter of Uranus or Neptune.…”
Section: Occultations Of Narrow Dense Ringsmentioning
confidence: 99%
“…At λ = 0.2µm, the great distances D of Uranus (19.2 AU) and Neptune (30 AU) from Earth prevent ground-based or Earth-orbit-based stellar occultations from obtaining better resolution than about 750 m and 950 m, respectively. Given that wave-like variations in the dense rings have sub-kilometer wavelengths (Chancia & Hedman 2016;Horn et al 1988), we expect resolutions of order 200 m is needed to see any planetgenerated waves. This resolution threshold, combined with the number of cuts required to uniquely determine the number of arms, which is of order the relevant m (about 20 for the waves of interest here), implies that the detection of planetary normal modes via wave identification will have to await an orbiter of Uranus or Neptune.…”
Section: Occultations Of Narrow Dense Ringsmentioning
confidence: 99%
“…The Uranian rings contain abundant km-scale structure, both radial and azimuthal, but much of it is uncharacterized and unexplained 38,39 . Furthermore, the Uranian rings could display oscillations that would allow for investigations of the interior structure of Uranus ('ring seismology'), similar to those that have led to advances in our understanding of the Saturnian interior 40 .…”
Section: Rings and Minor Satellitesmentioning
confidence: 99%
“…Thus, it is quite unlikely there are two or more undiscovered shepherding moons in this size range. Chancia & Hedman [27] have suggested that there might be small moons exterior to the α and β rings, based on wake-like patterns they detected in Voyager radio occultation data. However, their estimates of the moons' diameters, 4–14 km, may be difficult to reconcile with the sensitivity limits.…”
Section: The Main Uranian Rings and Their ‘Shepherding' Moonsmentioning
confidence: 99%